The Effect of Box Jump and Depth Jump Training on Long Jump Ability in PKO Students, Faculty of Sports and Health Sciences, Makassar State University (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of box jump and depth jump training on long jump performance among students of the Sports Coaching Education Program, Faculty of Sports and Health Sciences, Universitas Negeri Makassar. The research employed an experimental method using a two-group pretest-posttest design. A total of 30 students were randomly assigned to two groups: one received box jump training and the other depth jump training, both conducted over six weeks. Long jump ability was assessed before and after the training. Data analysis using the t-test revealed that both box jump and depth jump exercises had a significant impact on improving long jump performance (p < 0.05). Furthermore, a significant difference was found between the two methods, with depth jump training proving to be more effective than box jump training. It can be concluded that the depth jump is a more effective method for enhancing long jump performance in students. The initial test of the long jump ability of the box jump training group (A1) obtained a KS-Z value = 0.204 and a probability value = 0.094. Therefore, (P>0.05), this indicates that the initial test data follows a normal distribution or is normally distributed. The final test of the long jump ability of the box jump training group (A2) obtained a KS-Z value = 0.174 and a probability value = 0.200. Therefore, (P>0.05), this indicates that the final test data follows a normal distribution or is normally distributed. The initial test of the long jump ability of the depth jump training group (B1) obtained a KS-Z value = 0.202 and a probability value = 0.102. Therefore, (P>0.05), this indicates that the initial test data follows a normal distribution or is normally distributed. The final test of the long jump ability of the depth jump training group (B2) obtained a KS-Z value = 0.181 and a probability value = 0.200. Therefore (P>0.05), this shows that the final test data follows a normal distribution or is normally distributed.